Fosfatos de cálcio mesoporosos e como nanocompósitos com sílica: síntese, caracterização e ensaios de liberação controlada de fármaco - Fernandes, Ane Josana Dantas (2011)
The main application of calcium phosphates is as biomaterials, which are used as graft or bone implants. The preparation of mesoporous bioceramics allowed the use of these materials as drug carriers, as drugs incorporated into porous structure would be subsequently released upon grafting/implantation into the surrounding tissue in a controlled manner, with well-established kinetics. Improved chemical stability, particulary toward acids is a desirable feature of these biomaterials, as calcium phosphates dissolve at pH<4.00. The objectives of this work included the synthesis, characterization and application of calcium phosphate biomaterials, i.e., mesoporous hydroxyapatites and monetite/silica nanocomposites. The mesoporous hydroxyapatite was studied as drug carriers. The stability of the nanocomposites, prepared via the sol-gel method by varying the content of TEOS, were investigated with respect to chemical (acid) and thermal stability, including a detailed study on the thermal decomposition kinetics of for the second mass loss of monetite and the nanocomposite CaPSil2. Among the twenty one porous hydroxyapatites prepared using two cationic surfactants, the hexadecyltrimethylammonium bromide and myristyltrimethylammonium bromide and sodium dodecyl sulfate as anionic surfactant, at various concentrations, heating rates, and calcination temperatures, only HA-MTAB-60-673/5 was mesoporous, whereas the remaining one were nanoporous, as indicated by N2 adsorption isotherms. HA-MTAB-60-673/5 was forwarded to drug uptake and release studies. This material was synthesized using 60 mmol.dm-3 myristyltrimethylammonium bromide as surfactant; the hybrid mesostructure intermediate was heated at 5 K.min-1 to 673 K and calcinated isothermally at 673 K for 6 h under O2 to yield HA-MTAB-60-673/5 with surface area of 89 m2.g-1, pore volume of 0,56 cm3.g-1, and average pore diameter of 23.96 nm. Increasing calcination heating rate did not increase crystallinity. The solid was able to uptake the antibiotic benzyl penicillin-G in a 2012 mg.g-1 ratio (drug/support) in 10 min, which was ~ 9-fold greater than that of precursor hydroxyapatite. The drug release profile followed the Higuchi model with the release of 52% of the drug in a time of 41 h. The covalent incorporation of silica onto the monetite surface yielded four monetite/silica nanocomposites that had unit cell volume and crystallinity reduced as silica content increased. Increased immobilization reduced Q3 species, as shown by 29Si NMR, and contributed substantially to mass loss on TG studies. Calcium phosphate/silica nanocomposites were more stable toward acid dissolution than the respective phosphate precursor, particularly at pH<4.00. The kinetics of the second mass loss stage of the thermal decomposition of monetite and CaPSil2 was studied by non-isothermal methods. FWO method provided activation energies (Ea) of 200.87 and 228.14 kJ.mol-1 and Coats-Redfern method provided activation energies (Ea) of 178.43 and 165.84 kJ.mol-1 and pre-exponential factors (A) of 9.53 x 1013 and 1.16 x 1013 s-1 for monetite and CaPSil2, respectively. A good description of experimental data was achieved by using the Avrami-Erofeev nucleation model (A2).